Computer Anxiety, Academic Stress, and Academic Procrastination on College Students - Wahyu Rahardjo; Juneman Juneman; Yeni Setiani (Intelektual Pustaka Media Utama, 2013)
Academic procrastination is fairly and commonly found among college students. The lack of understanding in making the best use of computer technology may lead to anxiety in terms of operating computer hence cause postponement in completing course assignments related to computer operation. On the other hand, failure in achieving certain academic targets as expected by parents and/or the students themselves also makes students less focused and leads to tendency of postponing many completions of course assignments. The aim of this research is to investigate contribution of anxiety in operating computer and academic stress toward procrastination on students. As much as 65 students majoring in psychology became participants in this study. The results showed that anxiety in operating computer and academic stress play significant role in influencing academic procrastination among social sciences students. In terms of academic procrastination tendencies, anxiety in operating computer and academic stress, male students have higher percentage than female students.